Penggunaan Quizizz dalam Penilaian Pembelajaran pada Materi Ruang Lingkup Biologi untuk Meningkatkan Hasil Belajar Siswa Kelas X.6 SMAN 7 Banjarmasin - Sugian Noor (STKIP PGRI Banjarmasin, 2020)
Improving the quality of education is pursued by improving the learning process. Assessment of the learning process can be seen from changes that occur from the previous situation. Assessment of learning outcomes is an important component in learning activities. Instrument to achieve learning outcomes must pay attention to students' development and abilities. Most teachers use Assessment in the form of written tests. With the use of tests, the students are not impressed, so students' learning outcomes are low. quizizz is an alternative to do an assessment that is fun, and accountable and the assessment data can be known in real time according to the demands of the industrial revolution 4.0. Using quizizz will motivate children's thinking levels to be more fun and relaxed. The purpose of this study is to improve student learning outcomes. The subjects of this study were X.6 grade students consisting of 25 students. The results showed an increase from 58% to 85%, meaning an increase in the percentage of 27%. Based on the results of the study, it can be concluded that the use of Quizizz in the assessment of learning in the material of Biological Scope can improve the learning outcomes of class X.6 SMA 7 Banjarmasin of Academic Year 2018/2019.